Radixin Enhances Colon Cancer Cell Invasion by Increasing MMP-7 Production via Rac1-ERK Pathway - Qi-Hong Jiang; Ai-Xiang Wang; Yan Chen (The Scientific World Journal)
As a member of the ezrin-radixin-moesin (ERM) family, radixin is overexpressed in many tumor tissues. However, little is known about its role in the progression of colon cancer. So we here aimed to determine the function of radixin in colon cancer cell invasion. Interestingly, we found that the expression of radixin was significantly elevated in colon cancer cells. Knockdown of radixin suppressed the invasion and migration of colon cancer cells. Further, knockdown of radixin inhibited the activation of Rac1 and ERK1/2, and decreased the expression and secretion of MMP-7. In addition, Rac1-ERK signaling pathway was required for the radixin-promoted invasion and MMP-7 production. Together, our findings suggest that radixin enhances the invasion and migration of colon cancer cells. Activation of Rac1-ERK pathway and consequent upregulation of MMP-7 production may contribute to the function of radixin in the regulation of colon cancer cell invasion. Thus, radixin may act as a novel target for the diagnosis and treatment of colon cancer.